Néhány Árpád-kori oklevél emléke 1327. évi okiratokban - Almási Tibor (Acta Universitatis Szegediensis : acta historica, 1992)
A considerable number of mediaeval Hungarian documents did not survive in their original form, but their contents are preserved in transcripts or references. During the preparation of the archives of the Angevin era, among documents dating from 1327, several relics of documents originally from the Árpád era came to light. These relics had earlier been either forgotten or they had not been utilized by scholars. This study gives an account of four documents which were issued by members of the Árpád dynasty: Queen Elizabeth, mother of Ladislaus IV. and Kings Béla IV. and Stephen V. The author publishes the transcribed text of a document issued by Queen Elizabeth and reconstructs the contents of three other lost documents on the basis of subsequent references.